Assessment of Long-Term Proppant Conductivity - Wang, Jun; Xiong, Youming; Jiao, Guoying; Lei, Dengsheng (Frontiers in Energy Research, 2022)
Long-term conductivity data is very important to predict production performance of a fractured well. It is very necessary to know its long-term conductivity when choosing Tianxiang ceramic to prop a hydraulic fracture in Northwest China. Its long-term conductivity was evaluated using DL-2000 equipment. Testing time at each closure stress point was more than 7 hours though the procedure used was similar to the recommended practice for short-term proppant conductivity. This test also investigated how factors such as proppant concentration and proppant size affected long-term conductivity. The results show these factors have a significant effect on long-term conductivity. Conductivity increases as proppant concentration rises which is contributed to the increase of proppant volume and fracture height. Large proppant provides higher conductivity because large one has higher pore space. High experimental temperature reduces proppant conductivity due to the introduction of small fines and impurities. Conductivity declines with the increase of testing time, and therefore short-term conductivity value is bigger than long-term conductivity one while conductivity declines as testing time lasts. The achievements of this experiment will benefit hydraulic fracturing stimulation.